Nanocarriers: A Novel Approach for Enhanced Drug Delivery through Skin - Rode, Anuja (Asian Journal of Pharmaceutics (AJP), 2018)
In pharmaceuticals, about 90% of all medicines, active pharmaceutical ingredients are in the form of solid particles. With the development of nanotechnology, nanotechnology is a new approach within promising applications in the area of medicine, especially pharmaceutical for safe, controlled, and targeted drug delivery system. Nanotechnology is frequently applied in fiber textile, agriculture, electronics, forensic science, space, and medical therapeutics, namely, in disease detection, controlled drug delivery, as biosensors in tissue engineering. A nanocarrier drug delivery system formulation reduces the patient expenses and gives patient compliance. The major challenges in the development of nanoparticles as a drug delivery system are the control of particle size, surface properties and release of the active moiety to get the site-specific action at the desired rate and dose. Nanocarriers are being used as a transport moiety for another molecule. Nanocarriers are micelles, polymers, carbon-based materials, and liposome, and other substances are used for the delivery of drugs in the control or sustain release. Nanocarriers have recently been studied for their use in drug delivery for their unique characteristic use of chemotherapy. The colloidal system used in drug delivery with size ranging from 10 to 100 nm, use for sustained drug delivery system. In the present scenario nanotechnology has improved the diagnosis and treatment of dermatological conditions. The challenges associated with nanocarriers through the skin permeation are one of the hurdles, and it will soon overcome.